2023
DOI: 10.3389/fnins.2023.1154637
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-induced cerebellar transcriptomic changes in a postnatal model of fetal alcohol spectrum disorders: Focus on disease onset

Abstract: Fetal alcohol spectrum disorders (FASD) are a group of neurodevelopmental disorders caused by ethanol exposure in utero, which can result in neurocognitive and behavioral impairments, growth defects, and craniofacial anomalies. FASD affects up to 1-5% of school-aged children in the United States, and there is currently no cure. The underlying mechanisms involved in ethanol teratogenesis remain elusive and need greater understanding to develop and implement effective therapies. Using a third trimester human equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…These effects were relatively short-lived, lasting at least 6 days after the end of ethanol exposure on P4-9 and returning to baseline by adolescence (Cealie et al, 2023; C. J. M. Kane et al, 2021). It is exciting to see that investigators have been using state-of-the-art techniques to characterize the neuroinflammatory effects of ethanol in the cerebellum, including RNA sequencing (Holloway et al, 2023) and two-photon microscopy in vivo imaging (Cealie et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects were relatively short-lived, lasting at least 6 days after the end of ethanol exposure on P4-9 and returning to baseline by adolescence (Cealie et al, 2023; C. J. M. Kane et al, 2021). It is exciting to see that investigators have been using state-of-the-art techniques to characterize the neuroinflammatory effects of ethanol in the cerebellum, including RNA sequencing (Holloway et al, 2023) and two-photon microscopy in vivo imaging (Cealie et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The final number of papers that were decided to be included for the final data extraction was 98 (Fig 1). The search was re-run on September, 2023 for articles published between 2022-2023 and 6 additional papers were determined to fit the inclusion criteria (Boateng et al, 2023;Carugati, Goodlett, Cudd, & Washburn, 2022;Cealie et al, 2023;Fraize et al, 2023;Holloway et al, 2023;Todd, Clapp, Dains, Karacay, & Bonthius, 2022).…”
Section: Search Strategy and Study Selectionmentioning
confidence: 99%
“…Fetal Alcohol Syndrome (FAS) is a public health problem with a prevalence of 2–5% in the USA. FAS disturbs the structure and function of the brain, but the underlying mechanisms remain elusive (Holloway et al, 2023 ). Zheng et al , observed loss of the tubulin-binding cofactor B resulting in disorganized microtubules and shortening of astrocytic processes in a model of chronic alcohol exposure.…”
mentioning
confidence: 99%